Height Measurement and Adjustment of Welding Torch for Linear Welding Robot - Caetano, Lucas; Debiaze, Debora; Leivas, Eduardo; Steffens, Cristiano; Pernambuco, Bryan; Faria, Matheus; Drews, Paulo; Botelho, Silvia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Welding procedures are among the most commonly encountered processes in the industrial environment. They can be found in many areas within the modern industry, such as the manufacturing of metallic parts, construction of naval and offshore structures and others. Welding is not only an important task but also is a hazardous one. The process itself creates an environment of extreme heat and fumes, that is harmful to the welder's health. Thus, the robotization makes possible to move the welder away from the welding environment, bringing more quality when compared to manual welding. A robotic system is also able to perform a more reliable and faster welding. Another effect of moving away the operator is the increase its safety since welders have a high risk of developing occupational illness due to long exposure to the welding. An important aspect of the welding not yet fully automated is the contact tip to work distance (CTWD) adjustment, which involves the correct measurement of the distance between the welding torch and the surface to be welded. In this paper, a method to make the fine adjustment of this important parameter in real-time is presented. Thus, increasing the safety and the quality of the process.